Open Architecture Control for CNC System â€“ An Approach - M. Mankar, Amit; L. Shrivastava, R.; P. Giri, Jayant (International Journal of Engineering and Technology, 2018)
The Open Architecture concept is gaining more attention because of growing demand from end users. Numerical Control systems are limited in terms of portability because they are dependent on vendor-specific environment, to overcome this limitation Open Architecture Control was introduced. Open Architecture improves portability, interoperability, scalability and ability to reconfigure of an existing CNC machine. Open control system increases the flexibility of CNC machine by allowing vendor-neutral environment. Open Architecture Controller allows the end user to modify the existing system by integrating components from different manufacturers which reduce cost as well as increase extendibility of the system. In this review paper, different initiatives and developments on Open Architecture Controller are presented. This paper also covers the approaches made by researchers in the field of simulation of table movement in CNC machine.Â Â